Impact of relocation and reconstruction policies on the upgrading of urban industrial structure in old industrial districts - Lin, Qixing; Luo, Xiang; Lin, Guodong; Yang, Tiantian; Su, Wenjie (Frontiers in Environmental Science, 2022)
Old industrial bases (municipal districts) play a decisive role in the process of China's economic development. This study focuses on the upgrading of urban industrial structure. Based on the panel data of 120 old industrial bases (municipal districts) in China from 2010 to 2018, a double difference model was established to empirically analyze the impact of pilot relocation and reconstruction policies on the upgrading of urban industrial structure in old industrial districts. The results demonstrate that 1) The pilot relocation and reconstruction policies play a significant role in promoting the upgrading of urban industrial structure in old industrial districts; 2) Upgrading of urban industrial structure is significantly affected by the urban economic development level, urban population density, land marketization level, industrial enterprise agglomeration degree and infrastructure construction; 3) The impact of relocation and reconstruction policies on the upgrading of urban industrial structure in old industrial districts exhibits certain regional heterogeneity. Finally, the study proposes some targeted suggestions for future formulation of effective policies for the relocation and reconstruction of old industrial areas and optimal allocation of urban industrial structure.